Probiotics fortify intestinal barrier function: a systematic review and meta-analysis of randomized trials - Zheng, Yanfei; Zhang, Zengliang; Tang, Ping; Wu, Yuqi; Zhang, Anqi; Li, Delong; Wang, Chong-Zhi; Wan, Jin-Yi; Yao, Haiqiang; Yuan, Chun-Su (Frontiers in Immunology, 2023)
Background Probiotics play a vital role in treating immune and inflammatory diseases by improving intestinal barrier function; however, a comprehensive evaluation is missing. The present study aimed to explore the impact of probiotics on the intestinal barrier and related immune function, inflammation, and microbiota composition. A systematic review and meta-analyses were conducted. Methods Four major databases (PubMed, Science Citation Index Expanded, CENTRAL, and Embase) were thoroughly searched. Weighted mean differences were calculated for continuous outcomes with corresponding 95% confidence intervals (CIs), heterogeneity among studies was evaluated utilizing I2 statistic (Chi-Square test), and data were pooled using random effects meta-analyses. Results Meta-analysis of data from a total of 26 RCTs (n = 1891) indicated that probiotics significantly improved gut barrier function measured by levels of TER (MD, 5.27, 95% CI, 3.82 to 6.72, P < 0.00001), serum zonulin (SMD, -1.58, 95% CI, -2.49 to -0.66, P = 0.0007), endotoxin (SMD, -3.20, 95% CI, -5.41 to -0.98, P = 0.005), and LPS (SMD, -0.47, 95% CI, -0.85 to -0.09, P = 0.02). Furthermore, probiotic groups demonstrated better efficacy over control groups in reducing inflammatory factors, including CRP, TNF-α, and IL-6. Probiotics can also modulate the gut microbiota structure by boosting the enrichment of Bifidobacterium and Lactobacillus. Conclusion The present work revealed that probiotics could improve intestinal barrier function, and alleviate inflammation and microbial dysbiosis. Further high-quality RCTs are warranted to achieve a more definitive conclusion. Clinical trial registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=281822, identifier CRD42021281822.